Notes on the emerging accreditation regimes in Australia and New Zealand - Kristian Boehringer; Fionna Scott; Sue Blyth (Laureate Education Inc, 2012)
In recent years, new higher education regulatory regimes have emerged in both New Zealand and Australia. In Australia, the new Tertiary Education Quality and Standards Agency (TEQSA) employs a risk management approach while New Zealand Quality Agency (NZQA) has adopted an evaluative approach. In practice, these varying approaches create real differences in the ways in which the regulatory regimes are applied. This paper considers one discreet but critical element of these new regulatory regimes, academic staff qualifications, as an example of the difference between the risk management and evaluative regulatory approaches. Unsurprisingly, the application of academic staff qualifications requirements is particularly an issue whenever a higher education provider seeks to deliver a new course of study. In order to do so, a higher education provider must seek regulatory approval, in both countries this is known as accreditation.  DOI: 10.18870/hlrc.v2i3.76